Bryofloristic component in phytobiota of the Landscape Reserve “Sagy” (Херсонська область) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The thirty eight moss species, two moss forms and five moss variations grow on the territory of Landscape Reserve “Sagy”. Chiefly, these species are typical components of the Nothern Black Sea Coast natural phytocoenosis. Two species – Porella platyphylla, Pseudocrossidium hornschuchianum – are “Regionally rare" bryophytes of the Kherson region. Place the growth of bryophytic tied up with psamophytic, marsh, meadow biotopes, with biotopes of alder groves, with birch groves (“sagy”) and pine planting. The bryoflora of the reserve is characterized by a variegated spectrum of families with nemoral-boreal species Amblystegiaceae, Mniaceae, Polytrichaceae, Hypnaceae, a noticeable predominance of the number of Brachytheciaceae species, and a low number of Orthotrichaceae species. We found that these briocomplexes had different structures and species diversity. The bryofloristic complexes of psammophytic biotopes (6 species) are similar to the poorer version of the psammophytic forbs-fescue-feather grass steppe bryoflora of the Southern Ukraine, in composition and structure of the moss layer. The difference between the moss cover of psammophytic biotopes of the «Sagy» reserve consists in fewer species of mosses, the absence of side-spore (pleurocarpous) bryophytes from the Polytrichaceae in the moss layer, as well as the low participation of representatives of the Bryaceae. The structure of meadows and the marshes marsh level in the “Sagy” reserve is similar to the depleted version of moss communities of the Lower Dnieper birch marshes without open water space; a characteristic feature, in addition to small species diversity, is the absence of representatives of the Sphagnopsida and Polytrichopsida classes. The bryophyte complex of pine plantations of the reserve (11 species ) is a depleted variant of coenobrioflor lichen pine forests, which were described for the sandy massifs of the Lower Dnieper. The moss complex of alder carpets (12 species) differs from the typical cenobrioflora of black alder forests characteristic of the Lower Dnieper reaches. It is similar to mossy overgrown trees in anthropogenic dendrocenoses (forest strips and forest parks), in species composition and spatial and structural characteristics. In our opinion, the briocomplex of alder sagas has been changed due to anthropogenic impact, namely because of fires. The list of bryophyte species found in birch «sagas» (23 species) partially coincides with the list of mossy floodplain Betula pendula forests, typical of the eastern part of the steppe zone of Europe. The moss complex of the investigated birch nuts is poorer, there are fewer representatives of the Amblystegiaceae family and epigene mosses, and the involvement of the epixel component is enhanced. These structural features can be seen as an example of the specific zonal flora of the natural dendrocenosis of the Northern Black Sea. Comparison of the bryocomplexes associated with the biotopes of the “Sagy” nature reserve showed that they illustrate the possible directions of the evolution of the bryoflora of the Lower Dnieper Sands in the case of a hypothetical humidization of the climate. Changes include an increase in the role of mesophytic and mesogygrophithous species of the Amblystegiaceae, Bryaceae, Brachytheciaceae families, an increase in the number of epixilous moss species in parallel with the preservation of the role of the epigeoid bryogroup.
Keywords: bryophlora, dendrocenosis, reserved natural areas, Northern Black Sea Coast region.